Challenges of case identification and diagnosis of Autism Spectrum Disorders in China: A critical review of procedures, assessment, and diagnostic criteria. (September 2018) - Pang, YanLi; Lee, Chimei M.; Wright, Morgan; Shen, Jiaming; Shen, Bo; Bo, Jin
Highlights: The estimated prevalence of ASD in China has been consistently reported to be lower than most of the studies in the West. The inconsistent diagnostic procedures and the variations assessment instruments affect the ASD identification in China. The discrepancies in diagnostic criteria between CCMD and two widely used systems (i.e., ICD and DSM) also impact the ASD diagnosis. Researchers and clinicians need to be aware of the challenges and develop strategies to improve the identification of ASD. Abstract: The estimated prevalence of Autism Spectrum Disorders (ASD) in China has been consistently lower than most of the studies in the West. The current article addressed several challenges in identifying and diagnosing ASD in mainland China. The underestimated prevalence may due to a variety of reasons, including inconsistencies in screening and diagnostic procedures, variations in translated instruments, and discrepancies between diagnostic criteria. This review provides insight into ASD assessment and diagnosis in the Chinese population and discusses strategies for the further advancement of ASD identification and intervention in mainland China.